Don't Take It 'Lytely': A Case of Acute Tetany - Johnson, McKenna M (Cureus, 2019)
The most common causes of tetany are hypocalcemia, hypomagnesemia, hypokalemia, and alkalosis. Most case reports of tetany in the literature include some combination of the above metabolic derangements leading to non-life-threatening symptoms. We present a unique case of severe life-threatening tetany in a 38-year-old female with a history of Crohn’s disease. She was previously dependent on total parenteral nutrition (TPN) but discontinued TPN two weeks prior to presentation due to the improvement of her Crohn’s symptoms with a new medication regimen. We propose that malabsorption led to multiple electrolyte abnormalities, resulting in acute tetany that subsequently caused rhabdomyolysis. This case reviews the most common causes of acute tetany and highlights the interaction between electrolytes implicated in both tetany and rhabdomyolysis. It also emphasizes the importance of considering tetany as a diagnosis in a patient with unstable vital signs and diffuse muscle spasms.